Effects and comparisons of a 16-week resistance training vs. yoga intervention on psychological distress in older adults - Huamin Mo; Yulong Li (Acta Psychologica)
Background and aims: Although resistance (RT) and yoga (YG) interventions have had positive effects on psychological distress, examining the efficiency and practical utility between the two has yet to be established. Therefore, the main purpose of the study was to examine the effects of RT and YG interventions on psychological distress in older adults. Methods: In this 16-week intervention study, participants were 86 community-dwelling older adults randomly assigned to the RT (N = 29), YG (N = 28) and control (CON, N = 28) groups. Psychological distress was assessed by the Kessler K10 questionnaire. Results: Over a follow-up period, YG group decreased psychological distress by 18.9 % (31.7 ± 5.5 at baseline vs. 25.7 ± 5.6 at follow-up, ES = 1.08, p < 0.001). For RT group, psychological distress decreased by 18.5 % (31.3 ± 8.2 vs. 25.5 ± 5.8, ES = 0.82, p < 0.001). CON group increased psychological distress by 19.8 % (31.8 ± 4.3 vs. 38.1 ± 7.0, ES = 1.08, p < 0.001). No significant differences in effect size (ES) between the YG and RT groups were observed, indicating similar effects on psychological distress. Conclusion: This study shows that RT and YG interventions have similar and positive effects in lowering the level of psychological distress. Thus, both strategies may be safely implemented as non-pharmacological therapies in clinical practice to target high psychological distress in older adults.